Identity Bias in Negative Word of Mouth Following Irresponsible Corporate Behavior: A Research Model and Moderating Effects - Antonetti, Paolo (Journal of business ethics, 2018)
Current research has documented how cases of irresponsible corporate behavior generate negative reactions from consumers and other stakeholders. Existing research, however, has not examined empirically whether the characteristics of the victims of corporate malfeasance contribute to shaping individual reactions. This study examines, through four experimental surveys, the role played by the national identity of the people affected on consumers’ intentions to spread negative word of mouth (WOM). It is shown that national identity influences individual reactions indirectly; mediated by perceived similarity and sympathy. Consumers perceive foreign victims as different from the self and this reduces the sympathy experienced towards them. Sympathy is an emotion that shapes consumer reactions and regulates WOM. The study identifies two moderating processes of this effect. Individuals who score high on collective narcissism are most likely to be strongly biased against foreign victims. In-group bias is also moderated by the perceived severity of the crisis. When a case is perceived as very serious, perceived similarity plays a less important role in generating sympathy because consumers focus on the perceived suffering of the victims. Hence, in-group bias is stronger in cases perceived as having minor consequences. The paper contributes to the literature on corporate social irresponsibility and offers implications for both scholars and managers.